Daratumumab for patients with myeloma with early or late relapse after initial therapy: subgroup analysis of CASTOR and POLLUX - Spencer, Andrew; Moreau, Philippe; Mateos, Maria-Victoria; Goldschmidt, Hartmut; Suzuki, Kenshi; Levin, Mark-David; Sonneveld, Pieter; Orlowski, Robert Z.; Yoon, Sung-Soo; Usmani, Saad Z.; Weisel, Katja; Reece, Donna; et al. (Blood advances, 2024)
High-risk multiple myeloma (MM) is often defined based on cytogenetic abnormalities, but patients who relapse early after initial therapy are considered a functional high-risk group. In the phase 3 CASTOR and POLLUX studies, daratumumab plus bortezomib/dexamethasone (D-Vd) or lenalidomide/dexamethasone (D-Rd) improved progression-free survival (PFS) and overall survival (OS), regardless of cytogenetic risk, and achieved higher rates of complete response or better (≥CR) and minimal residual disease (MRD) negativity vs that with Vd/Rd alone in relapsed/refractory MM. Post hoc analyses of CASTOR and POLLUX evaluated patient subgroups with 1 prior line of therapy based on timing of progression/relapse (early or late) after initiation of first line of therapy. PFS consistently favored the daratumumab-containing regimens across subgroups using both a 24- and 18-month early-relapse cutoff. In the CASTOR/POLLUX pooled data set, daratumumab reduced the risk of disease progression or death by 65% (hazard ratio [HR], 0.35; 95% confidence interval [CI], 0.26-0.48; P < .0001) in the early-relapse (<24 months) subgroup and by 65% (HR, 0.35; 95% CI, 0.26-0.47; P < .0001) in the late-relapse (≥24 months) subgroup. OS also favored the daratumumab-containing regimens in both the early-relapse (HR, 0.62; 95% CI, 0.45-0.86; P = .0036) and late-relapse (HR, 0.67; 95% CI, 0.48-0.93; P = .0183) subgroups in the pooled population using a 24-month cutoff. Rates of ≥CR and MRD negativity (10−5) were higher with daratumumab vs control, regardless of progression/relapse timing. Although daratumumab is unable to fully overcome the adverse prognosis of early relapse, our results support the use of daratumumab for patients with 1 prior line of therapy, including for those who progress/relapse early after initial therapy and are considered to have functional high-risk MM. These trials were registered at www.clinicaltrials.gov as #NCT02136134 (CASTOR) and #NCT02076009 (POLLUX).
Vorab veröffentlicht: 4. Dezember 2023
Gesehen am 12.11.2024